Investing in Human Capital for Green and Sustainable Development - BEISEMBINA, Ansagan; GIZZATOVA, Alla; KUNYAZOV, Yerlan; ERNAZAROV, Takhir; MASHRAPOV, Nurlan; DONTSOV, Sergey (Journal of Environmental Management and Tourism, 2023)
Green and sustainable development is crucial for addressing environmental challenges and promoting a more sustainable future. Central to this endeavor is the investment in human capital, which involves developing and empowering individuals with the knowledge, skills, and mindset necessary to contribute and lead sustainable development efforts. Explores the importance of investing in human capital and the various ways in which it can be fostered to drive green and sustainable development. An analysis was made in the areas of investments in health care, education and environmental protection in order to develop a sustainable green development of the economy.